Perspectives on scientific error - D. van Ravenzwaaij; M. Bakker; R. Heesen; F. Romero; N. van Dongen; S. Crüwell; S. M. Field; L. Held; M. R. Munafò; M. M. Pittelkow; L. Tiokhin; V. A. Traag; et al. (Royal Society Open Science, 2023)
Theoretical arguments and empirical investigations indicate that a high proportion of published findings do not replicate and are likely false. The current position paper provides a broad perspective on scientific error, which may lead to replication failures. This broad perspective focuses on reform history and on opportunities for future reform. We organize our perspective along four main themes: institutional reform, methodological reform, statistical reform and publishing reform. For each theme, we illustrate potential errors by narrating the story of a fictional researcher during the research cycle. We discuss future opportunities for reform. The resulting agenda provides a resource to usher in an era that is marked by a research culture that is less error-prone and a scientific publication landscape with fewer spurious findings.